Rainfall intensity characteristics at coastal and high altitude stations in Kerala - V Sasi Kumar, S Sampath, P V S S K Vinayak and R Harikumar (J. Earth Syst. Sci. 116, No. 5, October 2007, pp. 451-463, 2007)
Rainfall intensities measured at a few stations in Kerala during 2001-2005 using a disdrometer were found to be in reasonable agreement with the total rainfall measured using a manual rain gauge. The temporal distributions of rainfall intensity at different places and during different months show that rainfall is of low intensity (<10mm/hr), 65 per cent to 90 per cent of the time. This could be an indication of the relative prevalence of stratiform and cumuliform clouds. Rainfall was of intensity <5mm/hr for more than 95 per cent of the time in Kochi in July 2002, which was a month seriously deficient in rainfall, indicating that the deficiency was probably due to the relative absence of cumuliform clouds. Cumulative distribution graphs are also plotted and fitted with the Weibull distribution. The fit parameters do not appear to have any consistent pattern. The higher intensities also contributed significantly to total rainfall most of the time, except in Munnar (a hill station). In this analysis also, the rainfall in Kochi in July 2002 was found to have less presence of high intensities. This supports the hypothesis that the rainfall deficiency was probably caused by the absence of conditions that favoured the formation of cumuliform clouds